ESTONIAN E-TAXATION EXPERIENCE AND PROSPECTS OF ITS ADAPTATION TO UKRAINE - Matveichuk L.O. (Pressing Problems of Public Administration, 2015)
The article analyzes the worldwide development of e-governments based on the most authoritative international assessments. The current state of Estonia’s e-tax management is investigated to take into account its benefits for the development of e-governance programs in Ukraine expected to create good governance and transparency in government.